ANALISIS PENERAPAN MODEL PEMBELAJARAN PADA KONDISI TATAP MUKA TERBATAS MATA PELAJARAN BIOLOGI DI MAN 1 PALEMBANG - Meli Astriani; Cecilia Indriani; Saleh Hidayat; Sri Wardhani (BIOEDUKASI (Jurnal Pendidikan Biologi), 2022)
The learning process is limited, causing the learning carried out by the teacher to be less than optimal. Teachers only carry out learning activities with limited time. The purpose of this study was to determine the use of learning models, the use of media and technology, and to find out the obstacles to the use of learning models. This type of research uses a form of qualitative research with descriptive methods. The population and sample in the study included MAN 1 Palembang with the research subjects being biology teachers and students in grades X, XI, and XII. Data collection techniques used observation, interviews, and documentation. The results showed that: (i) The implementation of biology learning carried out by teachers during face-to-face learning was limited to using conventional learning models including questions and answers and lectures so that learning only slightly involved active students. The use of media and teaching materials only comes from youtube, LKPD, and handbooks, (ii) Constraints in the application of learning models during face-to-face are limited, namely, the teacher's difficulty in explaining the material because the learning time only lasts 30 minutes so it is difficult for teachers to manage time when using syntax learning models and teachers' knowledge of learning models are also still low; (iii) limited face-to-face learning has not been able to improve student learning outcomes. The results of the research become a form of evaluation for madrasas so that teachers continue to pay attention to professional and pedagogic competencies as teacher role models in the 21st century.Kata kunci: Biologi, Model Pembelajaran, Tatap Muka Terbatas, Pandemi